KEKUATAN PEMBUKTIAN DIGITAL SIGNATURE PADA PERJANJIAN E-COMMERCE BERDASARKAN UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Erniwati Erniwati; Meirina Dewi Pratiwi (Justici, 2021)
Both the digital signature and the conventional signature both have different media, but basically the use of a digital signature or a conventional signature is an act that has the same legal consequences, namely giving birth to a legal relationship between the parties making the agreement. Now with the existence of the ITE Law as positive law, electronic deeds are considered the same as conventional deeds, as well as electronic signatures whose power of proof will be considered the same as manuscript signatures. This is regulated in Law No. 11 of 2008 on Information and Electronic Transactions in accordance with article 11 of the ITE Law